Effect of SiO2 on thermal conductivity of methane - Yuanchao LIU; Tingting ZHAO; Xinhao LIU; Yuanning WANG (Journal of Hebei University of Science and Technology)
In view of the lack of research on the microscopic thermal conductivity mechanism in the formation of methane hydrate in porous media, a molecular dynamics method was proposed to simulate the porous media gap model composed of SiO2. According to the microstructure of the simulated system, EMD method and NEMD method were proposed to study the thermal conductivity change process of the homogeneous solution in the SiO2 gap, and the molecular conformation diagram and density distribution cloud diagram of SiO2 intact gap and defect gap were analyzed. The influence law of SiO2 on the thermal conductivity in the initial stage of methane hydrate formation was obtained and the microscopic mechanism was analyzed. The results show that the mean thermal conductivity of the homogeneous solution with SiO2 gap obtained by EMD method is 0.53 W/（m·K）, and that of the homogeneous solution is 0.74 W/（m·K）. The thermal conductivity of homogeneous solution, intact SiO2 gap and defective SiO2 gap obtained by NEMD method is 0.986, 0.581 and 0.439 W/（m·K）, respectively. The EMD method and NEMD method are used to verify that the existence of SiO2 gaps is conducive to the formation and storage of methane hydrate, and the simulated thermal conductivity values are close to the measured values. SiO2 containing gaps can significantly reduce the thermal conductivity of the simulated system, which is conducive to the formation and storage of methane hydrate.